PERBEDAAN BATANG BAWAH DAN MASA PENYIMPANAN ENTRES TERHADAP PERTUMBUHAN OKULASI BIBIT JERUK SIAM MADU (Citrus nobilis) - Eko Wahyudi; Indah Permanasari; Ervina Aryanti (Jurnal Agroteknologi, 2017)
ABSTRACTThis research had been conducted from December to March 2015 at Horticultural Seed Center, Marpoyan, Pekanbaru. The study aimed to determine the effect of the type of rootstock and the storage period of buds as well as the interaction between both of them towards  its growth. This study was conducted experimentally by using completely randomized factorial design (CRFD) consisting of two factors and seven replications. The first factor was type of rootstock (B1: Japanese Citroen, B2: Rough Lemon) and the second factor was storage period of buds (M0: directly grafted, M1: 1-day storage period, M2: 2-day storage period, M3: 3-day storage period). Parameters measured were growth percentage of buds, bud burst time, length of buds, number of leaves and diameter of buds. The results showed that the Rough Lemon rootstock had a significant effect on the number of leaves, length of buds, bud burst time, diameter of buds and equally effect on the growth percentage of buds. Storage period of the buds did not significantly affect the growth of the grafted Siam Madu citrus seedlings.. The interaction between the type of rootstock and the storage period of buds only occurred in the bud burst time only.